CSR motives on situational scepticism towards luxury brands. Issue 1 (31st August 2021) - Teah, Kevin; Sung, Billy; Phau, Ian
Abstract : Purpose: The purpose of this study is to examine how perceived corporate social responsibility (CSR) motives may influence situational scepticism towards luxury brands and its effects on brand resonance, resilience to negative information and consumer advocacy of luxury brands. The moderating role of perceived fit towards luxury brand CSR initiatives is also investigated. Design/methodology/approach: An experimental approach on a 2 × 2 matrix was used. Data are collected through a consumer panel. Findings: Values-driven motives were found to lead to lower consumer situational scepticism and egoistic-driven motives would lead to higher levels of consumer situational scepticism. While higher consumer situational scepticism leads to lower brand resonance, there is no significant relationship between scepticism and resilience to negative information and consumer advocacy. The findings also suggest that perceived fit moderates the relationship between consumer situational scepticism to resilience to negative information and consumer situational scepticism to consumer advocacy. Originality/value: The key originality of the study is that it provides empirical insights into situational scepticism of CSR initiatives and its influence in consumer and management outcomes in luxury brands.